Delivering public services to the underserved: Nonprofits and the Latino threat narrative. (12th June 2022) - Tremblay‐Boire, Joannie; Prakash, Aseem; Calderon, Maria Apolonia
Abstract: Some politicians employ harsh rhetoric demanding that government deny public services such as food, housing, and medical care to immigrants. While nonprofits assist immigrants in this regard, their work is sustainable only if private donors support them. Using a survey experiment, this article examines whether donors' willingness to support a charity depends on the legal status of its beneficiaries, and the region from which they have come. We find that, in relation to a charity that serves low‐income families (control group), donors are less willing to support a charity serving immigrants, but the region from which beneficiaries emigrated is irrelevant. Donor willingness diminishes substantially when beneficiaries are undocumented or face deportation. While shared ethnicity between donors and beneficiaries does not increase charitable support, bilingualism does. In addition, support for the charity rises substantially among Latinx donors who were born outside the US and do not speak English at home.